Built-In Nonlinear Characteristics of Low Power Operating One-Resistor Selector-Less RRAM by Stacking Engineering. (25th October 2017) - Chen, Ying-Chen; Chang, Yao-Feng; Lin, Chih-Yang; Wu, Xiaohan; Xu, Gaobo; Fowler, Burt; Chang, Ting-Chang; Lee, Jack C.
Abstract : The sneak-path leakage current issue is one of the severe hindrances for the application of high density resistive random access memory (RRAM) array design. In this work, we demonstrate nonlinear (NL) resistive switching characteristics of HfOx /SiOx -based stacking structure as a realization for selector-less RRAM devices. The NL characteristic was obtained and designed by optimizing internal filament location with low effective dielectric constant intending in HfOx /SiOx structure. The stacking HfOx /SiOx -based RRAM device as the one-resistor-only memory cell is applicable without additional selector device to solve the sneak-path issue with switching voltage 1 V, which is desirable for low power operating in built-in nonlinearity crossbar array configuration.